2007
DOI: 10.1109/tit.2007.896873
|View full text |Cite
|
Sign up to set email alerts
|

Accumulate–Repeat–Accumulate Codes: Capacity-Achieving Ensembles of Systematic Codes for the Erasure Channel With Bounded Complexity

Abstract: The paper introduces ensembles of accumulate-repeat-accumulate (ARA) codes which asymptotically achieve capacity on the binary erasure channel (BEC) with bounded complexity, per information bit, of encoding and decoding. It also introduces symmetry properties which play a central role in the construction of capacity-achieving ensembles for the BEC with bounded complexity. The results here improve on the tradeoff between performance and complexity provided by previous constructions of capacity-achieving ensembl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(110 citation statements)
references
References 29 publications
1
109
0
Order By: Relevance
“…For various families of code ensembles, Table I compares the number of iterations and the graphical complexity which are required to achieve a given fraction 1 − ε (where ε can be made arbitrarily small) of the capacity of a BEC with vanishing bit erasure probability. The results in Table I are based on lower bounds and some achievability results which are related to the graphical complexity of various families of code ensembles defined on graphs (see [8], [9], [11], [12]); the results related to the number of iterations are based on the lower bounds introduced here (for rigorous proofs, see [13] families of code ensembles (including LDPC codes, systematic and non-systematic IRA codes, and ARA codes), the number of iterations which are required to achieve a fixed bit erasure probability scales at least like the inverse of the gap between the channel capacity and the design rate of the ensemble. This conclusion holds provided that the fraction of degree-2 variable nodes in the Tanner graph does not vanish as the gap to capacity vanishes (where under mild conditions, this property is satisfied for sequences of capacity-achieving LDPC code ensembles, see [10,Lemma 5]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For various families of code ensembles, Table I compares the number of iterations and the graphical complexity which are required to achieve a given fraction 1 − ε (where ε can be made arbitrarily small) of the capacity of a BEC with vanishing bit erasure probability. The results in Table I are based on lower bounds and some achievability results which are related to the graphical complexity of various families of code ensembles defined on graphs (see [8], [9], [11], [12]); the results related to the number of iterations are based on the lower bounds introduced here (for rigorous proofs, see [13] families of code ensembles (including LDPC codes, systematic and non-systematic IRA codes, and ARA codes), the number of iterations which are required to achieve a fixed bit erasure probability scales at least like the inverse of the gap between the channel capacity and the design rate of the ensemble. This conclusion holds provided that the fraction of degree-2 variable nodes in the Tanner graph does not vanish as the gap to capacity vanishes (where under mild conditions, this property is satisfied for sequences of capacity-achieving LDPC code ensembles, see [10,Lemma 5]).…”
Section: Discussionmentioning
confidence: 99%
“…Ensembles of irregular and systematic ARA codes, which asymptotically achieve the capacity of the BEC with bounded graphical complexity, are presented in [9]. This bounded complexity result stays in contrast to LDPC code ensembles, which have been shown to require unbounded graphical complexity in order to approach channel capacity, even under maximumlikelihood decoding (see [11]).…”
Section: A Accumulate-repeat-accumulate Codesmentioning
confidence: 99%
See 2 more Smart Citations
“…ARA codes were introduced by Abbasfar, Divsalar, and Kung in [7]. Later, it was shown that the DE analysis of IRA and ARA codes can be reduced to the DE analysis of LDPC codes via a technique known as graph reduction [8].…”
Section: Introductionmentioning
confidence: 99%